E-041 Is there an Interventional Role in Thyrotoxic Crisis?. (14th July 2013) - Morgan, R; Best, S; Connor, C; Johnson, P; Madarang, J
Abstract : Learning Objectives: Provide a clinical review of thyrotoxic crisis (thyroid storm). Review the limited published data currently available on thyroid arterial embolisation as treatment of thyrotoxic crisis. Provide pictorial anatomic review of thyroid arterial supply. Present a case of thyrotoxic crisis refractory to medical management and unsuitable for surgical intervention, which underwent thyroid arterial embolisation. Background: Thyrotoxic crisis is an acute exacerbation of thyrotoxicosis, which can be precipitated by a multitude of causes. It has an overall mortality rate of20–30%, however if treatment is delayed the mortality rate increases up to approximately 75%. Treatment requires vigorous medical management and while thyroidectomy is often necessary, the severity of the exacerbation often makes this patient population poor surgical candidates. A limited number of published case reports demonstrate thyroid arterial embolisation as a treatment options for unstable patients with thyrotoxic crisis. Embolisation is via the bilateral superior and inferior thyroid arteries. Clinical Findings/Procedure Details: This poster presents will review a case of a 69 year old male with intractable thyrotoxic crisis, despite appropriate medical management. The patient was not a surgical candidate due to prior episodes of cardiac and respiratory arrest secondary to sustained ventricular fibrillation. Given the patient's overall poor prognosis and lack of treatment options, arterial embolisation of the thyroid was considered. The patient underwent bilateral superior and inferior thyroid artery embolisations using 500 to 700 micron embospheres. Following embolisation there was interval increase in T4 and T3, as previously reported, but no further episodes of sustained ventricular fibrillation occurred and a curative thyroidectomy was performed one week later. Conclusion: The case report in combination with the limited published data suggests thyroid embolisation may have a role in treatment of nonsurigical refractory thyrotoxic crisis. Further research is needed to determine if thyroid embolisation could help reduce the high mortality rate associated with thyrotoxic crisis. Disclosures: R. Morgan: None. S. Best: None. C. Connor: None. P. Johnson: None. J. Madarang: None.